Adaptive Shape based Interactive Approach to Segmentation for Nodule in Lung CT Scans - Sathesh, A. (Journal of Soft Computing Paradigm, 2020)
In lung cancer diagnosis, growth of pulmonary nodule should be detected perfectly. Mostly watershed segmentation methods play a very important role in lung CT images to detect their growth. But this method detection will be ineffective in terms of energy function and speed as well. The proposed modified graph-cut technique is providing the good performing result in the speed and accuracy of the process than the conservative graph cut methods. Also, this research paper is proposed adaptive shape based interactive approach to segmentation for lung CT scan image and provide a more efficient. This proposed algorithm is proving that the energy function of the system is lesser than old methods. In this research paper, applying shape-based technique in segmentation technique has been proposed and proved for better accuracy with low energy function.